The Relationship Between Housing Policy and Local Development Policy in Romania. The Case of the Large Housing Estates Rehabilitation - Daniela-Luminita Constantin (European Regional Science Association (ERSA), 2006)
This paper represents a part of the author's contribution to the project "Housing rehabilitation in apartment block areas in Romania" developed under the auspices of the National Council for Higher Education Scientific Research. It addresses the relationship between housing policy and local development policy mainly from an institutional and legislative perspective, focusing on the actors involved in supporting housing and urban renewal actions in Romania. The role of local public administration is particularly envisaged, considering the authority of city councils with regard to rehabilitation of apartment block areas and, in a wider context, to urban regeneration. Several case studies on various Romanian cities will be presented in order to reveal not only current opportunities but also a series of drawbacks in this process.
Keywords: 330